Bevacizumab for Newly Diagnosed Ovarian Cancers: Best Candidates Among High-Risk Disease Patients (ICON-7). Issue 3 (4th April 2020) - Colomban, Olivier; Tod, Michel; Peron, Julien; Perren, Timothy J; Leary, Alexandra; Cook, Adrian D; Sajous, Christophe; Freyer, Gilles; You, Benoit
Abstract: Bevacizumab is approved as a maintenance treatment in first-line setting in advanced-stage III-IV ovarian cancers, because GOG-0218 and ICON-7 phase III trials demonstrated progression-free survival benefits. However, only the subgroup of patients with high-risk diseases (stage IV, and incompletely resected stage III) derived an overall survival (OS) gain in the ICON-7 trial (4.8 months). The modeled CA-125 elimination rate constant K (KELIM) parameter, based on the longitudinal CA-125 kinetics during the first 100 days of chemotherapy, is a potential indicator of the tumor primary chemo-sensitivity. In the ICON-7 trial dataset, the OS of patients within the low- and high-risk disease groups was assessed according to treatment arms and KELIM. Among the patients with high-risk diseases, those with favorable standardized KELIM of at least 1.0 (n = 214, 46.7%) had no survival benefit from bevacizumab, whereas those with unfavorable KELIM less than 1.0 (n = 244, 53.2%) derived the highest OS benefit (absolute difference = 9.1 months, 2-sided log-rank P  = .10; Cox hazard ratio = 0.78, 95% confidence interval = 0.58 to 1.04, 2-sided P  = .09).